IMPLEMENTASI PENDIDIKAN KARAKTER ANAK BERKEBUTUHAN KHUSUS (Universitas Negeri Semarang, 2015)
Penelitian ini bertujuan untuk melakukan studi terhadap implementasi pendidikan karakter anak berkebutuhan khusus dan menemukan model pada SD inklusi di Kabupaten Banyumas. Penelitian ini menggunakan pendekatan kualitatif. Pendekatan ini dipilih agar implementasi pendidikan karakter bagi anak berkebutuhan khusus pada SD inklusi di Kabupaten Banyumas dapat dideskripsikan secara faktual dan mendalam. Metode pengumpulan data yang digunakan dalam penelitian ini adalah wawancara, observasi dan studi dokumentasi. Analisis data dilakukan dengan model analisis interaktif. Teknik keabsahan data menggunakan teknik triangulasi data dan sumber. Hasil penelitian menunjukkan bahwa secara umum karakteristik pendidikan karakter anak berkebutuhan khusus pada SD inklusi di Kabupaten Banyumas menggunakan model pembiasaan. Implementasi pendidikan karakter yang digunakan menggunakan strategi-strategi terintegrasi dalam pembelajaran, pengembangan diri, dan penambahan alokasi waktu pembelajaran. Kendala yang dihadapi guru dalam implementasi pendidikan karakter adalah keterbatasan kemampuan siswa ABK, keterbatasan pengetahuan guru tentang ABK, kurang terbukanya orang tua siswa terhadap perkembangan anak, dan keterbatasan tenaga dan waktu guru serta banyaknya beban kerja. The aims of this research is to conduct a study on the implementation of character education of children with disabilities in inclusive Elementary School in Banyumas.This research use a qualitative descriptive approach. This approach is choosen, so that the implementation of character education for children with special needs in inclusive elementary school in Banyumas can be described factually and insightful. Data collection methods in this research are interviews, observation and documentation study.Data analysis is used by interactive analisiss models. Data validation techniques using triangulation techniques and sources of data.The results of the research show that the general characteristics of the character education of children with special needs in inclusive elementary school in Banyumas use a model of habituation. Implementation of character education use integrated strategies in learning, self-development, and additional learning time allocation. Constraints faced by teachers in the implementation of character education is the limited abilities of children who are special needs students, limited knowledge from teacher about children with special needs, parents are less open about their children development, and the limitations of time, energy and workloads of the teacher.The aims of this research is to conduct a study on the implementation of character education of children with disabilities in inclusive Elementary School in Banyumas.This research use a qualitative descriptive approach. This approach is choosen, so that the implementation of character education for children with special needs in inclusive elementary school in Banyumas can be described factually and insightful. Data collection methods in this research are interviews, observation and documentation study.Data analysis is used by interactive analisiss models. Data validation techniques using triangulation techniques and sources of data.The results of the research show that the general characteristics of the character education of children with special needs in inclusive elementary school in Banyumas use a model of habituation. Implementation of character education use integrated strategies in learning, self-development, and additional learning time allocation. Constraints faced by teachers in the implementation of character education is the limited abilities of children who are special needs students, limited knowledge from teacher about children with special needs, parents are less open about their children development, and the limitations of time, energy and workloads of the teacher.